Problematika Ketidakpatuhan Pelaporan Dana Kampanye dalam Pemilihan Bupati dan Wakil Bupati Lampung Tengah Tahun 2020 - Amir, Amir; Hertanto, Hertanto; Maryanah, Tabah (Lembaga Penelitian dan Pengabdian kepada Masyarakat of Universitas Islam Negeri Jurai Siwo Lampung, 2023)
Campaign funding is one of the determining factors for victory in the 2020 Lampung Tengah district head election competition. The transparency and accountability of campaign finance reports greatly determine the integrity of elections in Indonesia. This paper examines the campaign finance reports of the candidates for the 2020 election for regent and deputy regent of Central Lampung with a focus on aspects of receiving campaign funds, as well as compliance with applicable campaign finance regulations. Through a qualitative method using secondary data, in the form of a Report on Acceptance of Campaign Fund Contributions (LPSDK) it was found that the receipt of campaign funds for the 2020 pair of candidates for regent and deputy regent of Central Lampung was dominated by donations from candidate pairs and individual donations. The audit results show that the majority of candidate pairs are still not transparent and do not comply with campaign finance rules. Weak sanctions are suspected to be one of the causes, in addition to campaign finance regulations that have not regulated limits on campaign contributions from political parties and candidate pairs, as well as limits on spending on campaign funds so that the principle of equality and the principles of election justice are violated.